2022
DOI: 10.3390/met12122145
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4 Coated SiO2 Magnetic Nanoparticles for Enhanced Antibacterial Activity and Electrochemical Sensing

Abstract: Multifunctional magnetic composite nanoparticles (NPs) with antibiotics have demonstrated symbiotic effects because of their promising antimicrobial properties. The antimicrobial agent reduces side effects and dosage, and increases drug delivery efficiency. In this study, SiO2 coated over Fe3O4 magnetic nanoparticles (MNPs) were prepared by a solvothermal method. The MNPs were characterized by using X-ray diffraction (XRD), transmission electron microscopy (TEM), ultraviolet-visible spectroscopy (UV-vis), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The magnetic properties of SiO 2 -CaO-Na 2 O-P 2 O 5 -Fe 2 O 3 glasses and glass-ceramics, and SiO 2 coated Fe 3 O 4 core-shell nanoparticles have been investigated towards biomedical applications. [12][13][14]17,18,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] A survey of the literature shows that the magnetic properties of the above systems depend strongly on their composition and synthesis route. Rehman et al reported a sol-gel derived mesoporous magnetic glass-ceramic with a composition of 7Fe 3 O 4 -51SiO 2 -18CaO-20Na 2 O-4P 2 O 5 (mol%) containing Fe 3 O 4 with average particle size of 50 AE 10 nm and M s of B13 emu g À1 .…”
Section: Structural and Magnetic Properties Of Mnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic properties of SiO 2 -CaO-Na 2 O-P 2 O 5 -Fe 2 O 3 glasses and glass-ceramics, and SiO 2 coated Fe 3 O 4 core-shell nanoparticles have been investigated towards biomedical applications. [12][13][14]17,18,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] A survey of the literature shows that the magnetic properties of the above systems depend strongly on their composition and synthesis route. Rehman et al reported a sol-gel derived mesoporous magnetic glass-ceramic with a composition of 7Fe 3 O 4 -51SiO 2 -18CaO-20Na 2 O-4P 2 O 5 (mol%) containing Fe 3 O 4 with average particle size of 50 AE 10 nm and M s of B13 emu g À1 .…”
Section: Structural and Magnetic Properties Of Mnpsmentioning
confidence: 99%
“…11 Silica-coated magnetite nanoparticles have been extensively studied for various biomedical applications, including magnetic hyperthermia. [12][13][14][15][16][17][18] The cytotoxicity and magnetic properties of iron oxide-based 58S (58SiO 2 -33CaO-9P 2 O 5 ) bioactive glass and glass-ceramics have been investigated towards application in MHT. 19,20 Several ceramic compositions containing iron oxide have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…MEMS gas sensors are widely recognized to have a variety of applications because of their capacity for downsizing . Electrochemical, optical, and acoustic MEMS gas sensor types have all been created. , Different electrochemical gas sensors, including MOS and chemiresistive gas sensors, are employed in the detection of stomach infections and diabetes in addition to the monitoring of industrial gases. Higher sensitivity, low power consumption, multigas detection, selectivity to different gases, smaller designs, and lower production costs are some of its advantages over traditional gas sensors. ,, …”
Section: Factors Affecting Gas Sensing Of Nanocompositesmentioning
confidence: 99%